SUBDUCTION OF SOLAR-TYPE NOBLE GASES FROM EXTRATERRESTRIAL DUST: CONSTRAINTS FROM HIGH-PRESSURE LOW-TEMPERATURE METAMORPHIC DEEP-SEA SEDIMENTS - Schwarz W.H.; Trieloff M.; Altherr R. (My University, 2005)
Solar-type helium (He) and neon (Ne) in the Earths mantle were suggested to be the result of solar-wind loaded extraterrestrial dust that accumulated in deep-sea sediments and was subducted into the Earths mantle. To obtain additional constraints on this hypothesis, we analysed He, Ne and argon (Ar) in high pressure–low temperature metamorphic rocks representing equivalents of former pelagic clays and cherts from Andros (Cyclades, Greece) and Laytonville (California, USA). While the metasediments contain significant amounts of 4He, 21Ne and 40Ar due to U, Th and K decay, no solar-type primordial noble gases were observed. Most of these were obviously lost during metamorphism preceding 30km subduction depth. We also analysed magnetic fines from two Pacific ODP drillcore samples, which contain solar-type He and Ne dominated by solar energetic particles (SEP). The existing noble gas isotope data of deep-sea floor magnetic fines and interplanetary dust particles demonstrate that a considerable fraction of the extraterrestrial dust reaching the Earth has lost solar wind (SW) ions implanted at low energies, leading to a preferential occurrence of deeply implanted SEP He and Ne, fractionated He/Ne ratios and measurable traces of spallogenic isotopes. This effect is most probably caused by larger particles, as these suffer more severe atmospheric entry heating and surface ablation. Only sufficiently fine-grained dust may retain the original unfractionated solar composition that is characteristic for the Earths mantle He and Ne. Hence, in addition to the problem of metamorphic loss of solar noble gases during subduction, the isotopic and elemental fractionation during atmospheric entry heating is a further restriction for possible subduction hypotheses.
Keywords: noble gases; extraterrestrial dust